In silico analysis of secreted effectorome of the rubber tree pathogen Rigidoporus microporus highlights its potential virulence proteins - Longsaward, Rawit; Viboonjun, Unchera; Wen, Zilan; Asiegbu, Fred O. (Frontiers in Microbiology, 2024)
Rigidoporus microporus, the causative agent of the white root rot disease of rubber trees, poses a significant threat to natural rubber production worldwide. Understanding the molecular mechanisms facilitating its pathogenicity would be crucial for developing effective disease management strategies. The pathogen secretes effector proteins, which play pivotal roles in modulating host immune responses and infection. In this study, in silico analyses identified 357 putative secreted effector proteins from the R. microporus genome which were then integrated into previous RNA-seq data obtained in response to rubber tree latex exposure. Annotation of putative effectors suggested the abundance of proteins in several families associated with the virulence of R. microporus, especially hydrophobin proteins and glycoside hydrolase (GH) proteins. The contribution of secreted effectors to fungal pathogenicity was discussed, particularly in response to rubber tree latex exposure. Some unknown highly expressed effectors were predicted for the protein structures, revealing their similarity to aminopeptidase, ubiquitin ligase, spherulin, and thaumatin protein. This integrative study further elucidates the molecular mechanism of R. microporus pathogenesis and offers alternative targets for developing control strategies for managing white root rot disease in rubber plantations.